Predictors of Persistent Body Weight Misclassification from Adolescence Period to Adulthood: A Longitudinal Study - Abdulaziz Dakhel Aloufi; Jake Moses Najman; Abdullah Al Mamun (Springer, 2019)
This study examined whether body weight misclassification continues from adolescence to adulthood and the associated predictors behind that misclassification. Data are from a sample of a longitudinal Australian birth-cohort study. Data analyses were restricted to 2938 participants whose measured and perceived body weights were recorded during their adolescence and adulthood follow-ups. To identify misclassification, we objectively compared their measured and perceived body weights at each follow-up. Potential predictors during early life or adolescence periods were included in data analyses. At each follow-up, underestimation was recorded more often among overweight and obese participants, whereas overestimation was mostly recorded among underweight ones. Over 40% males and females were able to correctly estimate their body weight at one follow-up, whereas almost 30% males and 40% females were able to do so in more than one follow-ups. One-third females and 45% males underestimated their body weight at one follow-up, whereas 13% females and a quarter of males were able to do so in more than one follow-ups. Being female, dieting, being overweight, having an overweight mother, and having poor mental health were the most significant predictors for more than one follow-up misclassifications. Further studies are needed to evaluate the impact of persistent misclassification on population health benefits.